Assessment of U and As in groundwater of India: A meta-analysis. (September 2022) - Kumar, Vinod; Setia, Raj; Pandita, Shevita; Singh, Sumit; Mitran, Tarik
Abstract: More than 2.5 billion people depend upon groundwater worldwide for drinking, and giving quality water has become one of the great apprehensions of human culture. The contamination of Uranium (U) and Arsenic (As) in the groundwater of India is gaining global attention. The current review provides state-of-the-art groundwater contamination with U and As in different zones of India based on geology and soil texture. The average concentration of U in different zones of India was in the order: West Zone (41.07 μg/L) > North Zone (37.7 μg/L) > South Zone (13.5 μg/L)> Central Zone (7.4 μg/L) > East Zone (5.7 μg/L) >Southeast Zone (2.4 μg/L). The average concentration of As in groundwater of India is in the order: South Zone (369.7 μg/L)>Central Zone (260.4 μg/L)>North Zone (67.7 μg/L)>East Zone (60.3 μg/L)>North-east zone (9.78 μg/L)>West zone (4.14 μg/L). The highest concentration of U and As were found in quaternary sediments, but U in clay skeletal and As in loamy skeletal. Results of health risk assessment showed that the average health quotient of U in groundwater for children and adults was less than unity. In contrast, it was greater than unity for As posing a harmful impact on human health. This review provides the baseline data regarding the U and As contamination status in groundwater of India, and appropriate, effective control measures need to be taken to control this problem. Graphical abstract: Image 1 Highlights: Uranium (U) and arsenic (As) data in the groundwater of India were analyzed. The highest concentration of U was found in the West Zone of India. Arsenic concentration was found maximum in the South Zone of India. The concentration of U and As were maximum in quaternary sediments. The highest concentration of U and As were in clay skeletal and loamy skeletal soils, respectively.